Storage strategy of aerobic algae-bacteria granular consortia in photo-sequencing batch reactor. (20th August 2022) - Liu, Lin; Xin, Yu; Tong, Zhong-Hua; Zheng, Yu-Ming; Xie, Jia-Fang; Zhao, Quan-Bao; Yu, Han-Qing
Abstract: Aerobic algae-bacteria granular consortia (AAG) is a novel biotechnology for wastewater treatment, although the optimal storage operation is in favor of practical application and commercial production of AAG, the information about the performance response and microbial community evolution of AAG during storage process and activation process are still sparse. This experiment selected temperature, time and illumination condition as target parameters to firstly study the influence of storage process on the AAG. The results indicated that AAG could maintain the integrated granular structure under different storage conditions, yet the influence of storage conditions on the properties of AAG was significant. After storage and activation process, the specific removal rates of total phosphorus and ammonia nitrogen of AAG that stored at 25 °C were 1.41–1.98 mg/g SS and 15.44–17.92 mg/g SS, respectively, which were significantly higher than those stored at 4 °C and −25 °C (0.88–1.16 mg/g SS and 8.46–14.14 mg/g SS). The stored time showed significant negative relationship with the EPS concentration (R = −0.47, P < 0.001) and the polysaccharides/protein ratio (R = −0.50, P < 0.001) of AAG, while illumination was conducive to maintain the polysaccharides/protein ratio of AAG (R = 0.43, P < 0.05). In term of target microalgae viability ( Scenedesmus obliquus ), temperature and illumination were the significant factors explaining the change of its relative abundance in AAG at the end of activation process (P < 0.05), which contributed 64.9% and 33.1% of the variation, respectively. Holistic evaluation of seven storage strategies in this study by analytic hierarchy process furtherly indicated that the storage strategy with 25 °C of operational temperature, 30 d of storage time and protect from illumination was preferable for AAG (total weight score = 0.188), while cryopreservation was the least desirable (total weight score = 0.077). Graphical abstract: Image 1 Highlights: Illumination and shorter stored time are in favor of granular structure stability. Temperature that is conducive to algae survival can ensure nutrient removal rate. Normal temperature and illumination deficiency can guarantee Scenedesmus viability. Optimal storage strategy for AAG was determined based on holistic evaluation by AHP.